Work-family conflict, work-family facilitation, and coping as predictors of family satisfaction among female employees in Malaysia: a longitudinal study - Hussin, Ruhaya (2018)
This study aims to examine work-family conflict, work-family facilitation, and coping as predictors of family satisfaction. It was hypothesised that work-family conflict, work-family facilitation, and coping predict family satisfaction, both cross-sectionally and longitudinally. A longitudinal survey design with a six- to eight-month interval was used. Data was collected from 740 participants at Time 1 and 210 participants at Time 2 by using purposive sampling technique. Confirmatory factor analyses were conducted to check for the factor structures of each measure. Results from hierarchical multiple regression indicated that work-family conflict, work-family facilitation, and coping predicted family satisfaction at Time 1. However, only work-family conflict predicted family satisfaction at Time 2. Longitudinally, of all predictors. only work-family facilitation predicted family satisfaction. The results highlighted different contributions of work-family conflict, work-family facilitation, and coping as predictors of family satisfaction, both cross-sectionally and longitudinally. Implications of the present study and recommendations for future research are discussed.